Evaluasi Internal Aplikasi E-Monev pada Dinas Pekerjaan Umum dan Perumahan Rakyat (PUPR) Provinsi Jambi - Anna Maria Tampubolon; Yenny Yuniarti; Ade Perdana Siregar (MASMAN Master Manajemen, 2026)
This study aims to evaluate the effectiveness of the e-monev application at the Jambi Province Public Works and Public Housing Agency (PUPR) and to identify the constraints encountered in its management. The research used a qualitative descriptive method with data collection through in-depth interviews, observation, and documentation involving seven informants directly engaged in the application's management and operation. The analysis framework adopts the e-government success element theory by Indrajit (2002), comprising three dimensions: Support, Capacity, and Value. The findings reveal that the Support dimension is already strong, marked by leadership commitment, annual socialization and training, clear policy directives, and effective inter-unit coordination. In the Capacity dimension, human resource competence is generally adequate; however, technical constraints such as network instability, system slowdowns during concurrent access, and dependency on external programmers remain significant challenges. The Value dimension confirms that the e-monev application provides positive contributions to reporting efficiency, real-time monitoring, and data-based decision-making. Nevertheless, the overall effectiveness has not yet reached the optimal level due to persistent technical and infrastructure constraints. This study is expected to serve as an empirical basis for improving the quality of digital monitoring and evaluation systems in regional government agencies.